Hydrophobic functionalization of jute fabrics by enzymatic-assisted grafting of vinyl copolymers - Wu, Huimin (2017)
We report an eco-friendly approach to improve the hydrophobicity of jute fabrics via horseradish peroxidase (HRP)-catalyzed covalent grafting of butyl acrylate (BA) and 2,2,3,4,4,4-hexafluorobutyl methacrylate (HFBMA). Hydrophobic vinyl monomers were grafted onto the exposed lignin molecules of the jute surface by free-radical polymerization in the presence of a HRP/H2O2/acetylacetone (ACAC) system. Coupling onto the lignin-jute surface was demonstrated by attenuated total reflection-Fourier transform infrared spectroscopy (ATR-FTIR), solid-state nuclear magnetic resonance (solid-state 19F NMR), elemental analyses, X-ray photoelectron spectroscopy (XPS), energy-dispersive X-ray spectroscopy (EDS), matrix-assisted laser desorption/ionization mass spectrometry (MALDI-TOF MS) and scanning electron microscopy (SEM). The hydrophobicity and oleophobicity of modified jute fabrics was estimated in terms of contact angle and wetting time. The results indicated that it was essential to attain vinyl monomers grafting polymerization onto jute surfaces in a HRP/H2O2/ACAC system. Moreover, the grafting of vinyl monomers led to hydrophobicity increases of 53.86% and 61.03% in the contact angle of grafted jute fabrics with BA and HFBMA when compared with unmodified jute fabrics, respectively. Both vinyl monomers demonstrated high propensity to be polymerized by HRP in the presence of H2O2, and acquired the ability to act as high-performance composites with hydrophobic resins.